Spontaneous pneumomediastinum and pneumothorax in COVID‐19 patients: A tertiary care experience - Shaikh, Nissar (Health Sci Rep, 2021)
INTRODUCTION: COVID‐19 can occasionally complicate into spontaneous pneumothorax (SP) and/or spontaneous pneumomediastinum (SM). This study aims at exploring the occurrence of SP and or SM, risk factors, and outcomes in COVID‐19 patients. MATERIALS AND METHODS: All patients with COVID‐19, which complicated into SP and/or SM at Hamad Medical Corporation (the principal public healthcare provider in Qatar) from March to September 2020, were retrospectively enrolled. The clinical diagnosis was confirmed by CXR and CT. Between‐group comparisons were performed by using Chi‐square and t‐test. Differences were considered statistically significant at P ≤ .05. RESULTS: A total of 1100 patients were admitted, and 43 patients developed SP, SP + SM, or SM. Most patients were males (42/97.9%), and the most common comorbidity was diabetes mellitus (13/30.2%). All patients had acute respiratory distress syndrome (ARDS), and most patients had low lung compliance at the time of developing SP or SM. Twenty‐two of the patients developed SP (51.2%), 11 patients had both SP and SM (25.6%), and 10 patients had SM only (23.3%). There was no significant difference in the development of SP or SM and patients' gender or blood group or whether patients were on invasive or noninvasive ventilation or even the mortality (P > .05). Lung compliance was significantly (P < .05) lower in patients complicated with SP and or SM. Patients with SP required significantly higher (P < .001) chest drain insertion. CONCLUSION: Patients with severe COVID‐19 pneumonia can complicate into SP and SM. These complications are more common in male diabetic patients. Patients with ARDS and having low lung compliance are at a higher risk of developing SP, SP + SM, or SM.